Uma plataforma de comunicação universal utilizando protocolo Zigbee - Dallagasperina, Renato Weiller (2017)
With the rapid technological advancement, pervasive computing has gained more and more prominence. Nowadays, we easily find electronic devices embedded in common objects, bringing new functionalities and applications to these objects. This is being called Internet of Things (IoT), but in order to let the information collected or even remotely process it, the devices are dependent on a communication system, being a critical point in applications that must be reliable and highly available as well. The low offer of communication modules that enable transparent, reliable and user-friendly implementation often prevents the rapid development of applications in this area. Aiming to fill this gap, a hardware and software platform for wireless communication between devices was being developed using the Zigbee protocol. This platform is composed of two modules, one for short distances, up to 100 meters, and another for applications where the distance exceeds this value. The platform aims to facilitate the development of solutions for the most diverse areas, such as wireless sensor networks (WSNs), data collectors and actuators. For the validation of the platform, tests were carried out to check the energy consumption and behavior of the power system, as well as the verification of the transmission distance achieved, the capacity to form the network and the data transmission. After the validation, it was concluded that the platform presents characteristics of low power consumption, low cost and reliability in data transmission and network formation. The platform can be used as a universal platform to support the development of applications using the Zigbee protocol.